Adaptations to 60 versus 20 minutes of endurance training
The physiological adaptations that occur when training for 20 or 60 min at EN-1 intensity were evaluated. Implications: The often used adage of "speed through endurance training" is false. Endurance training alone has a detrimental effect on sprint swimming paces. Programs need to provide both aerobic and anaerobic training stimuli so that endurance and speed can be improved. For adequate aerobic development, at least 60 min of work at EN-1 or a higher intensity per day is required. If much more than 60 min of training is performed, the potential exists for swimming speed to be detrimentally affected. Endurance training should be substantial but not overdone. Since all races use both aerobic and anaerobic energy systems, training programs should attempt to develop each capacity from the late basic preparatory phase on.